Apakah Ibu Bekerja Mempengaruhi Asupan Anak dan Menyebabkan Kegemukan? Sebuah Penelitian Kasus Kontrol - Pricillia Wulandari; I Made Alit Gunawan; A Fahmy Arif Tsani (Poltekkes Kemenkes Yogyakarta, 2016)
Background:Nowadays, more mothers are choosing to work so they must divide their time between responsibilities. More time spent working will be reduce time for household chores, care and play with the children. Reduced time for household and child can affect food choices in children that can lead to obesity in children. Objective: to identify maternal employment as risk factor of obesity in preschool children and corelation between working hours and nutrition intake. Method:A case control study on preschool children aged 3-5 years, 101 cases have nutritional status weight-fot height: Obese (z-score> 2 SD), matching for age and sex with 101 controls that have nutritional status weight-fot height: normal (-2<z-score ≤2 SD). The study was conducted in the city of Yogyakarta early childhood during the months of June through October 2015. Information obtained through interviews with mothers using semi-quantitative FFQ questionnaire. Result:Maternal employment (OR 1.53; 95% CI: 0.80 to 3.00) and full time working hours (OR 1.57; 95% CI 0.88 to 2.86) was not statistically significant (p> 0 , 05) as risk factors of obesity in preschool children aged 3-5 years. Working hours was not statistically correlated (p> 0.05) with energy (r = -0.04), carbohydrate (r = -0.10), protein (r = -0.00), and fat (r = 0.02). Conclusion:Maternal employment and working hourswere not statistically significant as risk factors, but tend to increase likelihood of obesity in preschool children and there is no correlation between working hours and nutrition intake (energy, carbohydrates, protein, and fat) Key words: childhood obesity, maternal employment, preschool children, nutrition intake, working hours